Effect of intra-articular corticosteroid injections on pain and mouth opening in juvenile idiopathic arthritis with temporomandibular involvement: A systematic review and meta-analysis. Issue 8 (August 2020) - Antonarakis, Gregory S.; Blanc, Adrien; Courvoisier, Delphine S.; Scolozzi, Paolo
Abstract: Purpose: The objective of this study was to investigate the effect of temporomandibular intra-articular corticosteroid injections (IACS) on pain and mouth opening in children with juvenile idiopathic arthritis (JIA) with temporomandibular joint (TMJ) involvement. Methods: Systematic review and meta-analysis methodology was used, beginning with a comprehensive literature search using MEDLINE, PubMed, EMBASE, Web of Science, and the Cochrane library. The population in question was pediatric patients with a JIA diagnosis and TMJ involvement; the intervention was IACS injections to treat TMJ arthritis; a strict control group was not considered necessary; the outcome was clinical signs of improvement of the TMJ arthritis based on pain and mouth opening capacity (MIO). Data on pain and MIO were extracted from the selected studies, and the methodological quality of studies was assessed according to the ROBINS-I tool. Results from the different studies were combined to calculate the pooled proportion with 95% confidence intervals (CIs) for pain resolution, and pooled mean differences with 95% CIs for improvement in MIO. Heterogeneity of the results among studies was tested using I 2 statistics. Results: The initial search yielded a total of 330 articles; 11 of these were selected for inclusion in the review. 325 participants were included from the combined studies, with the mean age of participants ranging from 5.3 to 13.6 years. Between 24 and 137 TMJs were selected for each of the studies. The pooled proportion of patients with pain resolution following IACS injection was 78% (95% CI: 59–90%), with large heterogeneity ( I 2 = 62%). The pooled gain in MIO following IACS injection was 4.38 mm (95% CI: 2.76–6.00), also with high heterogeneity ( I 2 = 67%). Conclusions: The results suggest that in children diagnosed with JIA with TMJ involvement, IACS injections can help in reducing reported pain and improving mouth opening capacity, albeit with an important variation between studies.